A Note on -Potence Preservers on Matrix Spaces over Complex Field - Xiaofei Song; Chongguang Cao; Baodong Zheng (Abstract and Applied Analysis)
Let be the field of all complex numbers, the space of all matrices over , and the subspace of consisting of all symmetric matrices. The map satisfies that is -potent in implying that is -potent in , where then there exist an invertible matrix and with such that for every . Moreover, the inductive method used in this paper can be used to characterise similar maps from to .